Komunikasi Persuasif Pengasuh dalam Melakukan Pembinaan Akhlak Remaja di Panti Asuhan Aisyiyah Kota Pariaman - Nadia Salsabila Suardi Putri; Nunu Burhanuddin (Institut Nalanda, 2026)
This study examines the persuasive communication of caregivers in conducting moral development of adolescents at the Aisyiyah Orphanage in Pariaman City. The main problems in this study are: how is the persuasive communication process of caregivers in conducting moral development of adolescents at the Aisyiyah Orphanage in Pariaman City, what are the supporting and inhibiting factors of persuasive communication of caregivers in conducting moral development of adolescents at the Aisyiyah Orphanage in Pariaman City. The type of research used is a qualitative descriptive approach where this type of research attempts to collect facts through observation, interviews, and documentation. The researcher conducted observations at the Aisyiyah Orphanage in Pariaman City, in addition, the researcher also conducted in-depth interviews where the researcher conducted interviews with key informants and supporters, including the orphanage caregivers, orphanage children, and orphanage alumni. Based on the results of the study, the persuasive communication process in conducting moral development of adolescents at the orphanage uses appropriate language, clear goal setting, and overcoming rejection. Supporting factors include evidence and data, expertise, testimonials, stories or anecdotes, reasons and logic, consistency, social effects and benefits. Meanwhile, inhibiting factors include dogmatism, stereotypes, and environmental influences. Using appropriate language in everyday life is a crucial element in conveying the goals of persuasive communication.